Equal Opportunities and Ethnic Inequality in European Labour Markets Discrimination, Gender and Policies of Diversity - Wrench, John; Roosblad, Judith; Kraal, Karen (IMISCoe Reports, 2009)
The need to analyse labour market mechanisms in post-industrial Western societies is urgent. Despite laws and policy measures being developed at the European, national and local levels, job-seeking immigrants and ethnic minorities still suffer unequal access and ethnic discrimination. This volume endeavours to understand why. Four chapters dealing with discrimination, gender, equity policies and diversity management present a lively discussion of the current scientific debate. Besides providing empirical evidence, the authors recommend methods for conducting further research in the field and evaluate the actual effects of discrimination-combating policies. One conclusion is that systematic analysis of the labour market and its subsequent equity policies must be supported by hard data, such as statistics. With its state-of-the-art scope and unique thematic exploration, this volume transfers knowledge from social science studies to a more operational realm. From here, both scholars and practitioners can help make equal opportunities more accessible than ever.